Speaking after the Phenomenon: the Promise of Things and the Future of Phenomenology. Issue 48 (3rd April 2017) - Ó Murchadha, Felix
ABSTRACT: Phenomenology speaks not directly of phenomena but rather of the appearing of phenomena. In so speaking it moves from the level of things with generic or proper names to the level of universal terms. In speaking and thinking the phenomenon Phenomenology comes "after" in the twofold sense of being too late and desiring for that which is to come. This paper explores this place of phenomenology with respect to the relation of faith and reason, the manner of speaking phenomenologically and the affective and temporal situation of experience. Drawing on the pre-modern concept of the transcendentals and on an account of emphatic consciousness of things, this article argues that the future of phenomenology is as a form of metaphysics which remains focused on experience and the "promise" of things that guides and structures perception.